Hyperboles Used in The Song Lyrics of Bruno Mars: Figurative language, hyperboles, Bruno Mars, Song lyric - Sekeon, Trisya; Kamagi, Sarah; Kumayas, Tirza A. (JoTELL : Journal of Teaching English, Linguistics, and Literature, 2025)
The findings of the research, discussion and conclusion. The purposes of the research were to identify and to describe the types of hyperbolic expressions used in the song lyrics of famous male singer Bruno Mars. Descriptive method was applied in conducting the research. Ten popular songs sung by Bruno Mars became the focus entitled Grenade, Dancing with the Star, 24K Magic, Just the Way You Are, It Will Rain, Locked Out of Heaven, Versace on the Floor, Nothin’ on You, Lost and Talking to the Moon. The researcher only took those songs which were released from 2010 till the latest as sources of data. The data were collected and analysed by linguistic theory related to hyperboles as proposed by Christodoulidou (2011). The finding shows that there are 87 hyperbolic expressions found in song lyrics of Bruno Mars. There are 38 hyperboles in the song lyrics of Bruno Mars grouped as overstatement and the rest are 19 hyperboles grouped as hyperboles in impossible description. The first type becomes the most frequent hyperbole type used in the song lyrics of Bruno Mars and the second becomes the least. It can be concluded that hyperboles in song lyrics play powerful social functions and allow songwriters to convey complex emotions, create lasting impressions, and craft lyrics that resonate with a wide audience. The use of figurative language serves as an effective means to enhance the words employed in song lyrics.